2004
DOI: 10.1111/j.0023-5962.2004.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Public Subsidies Complement Business R&D? A Meta‐Analysis of the Econometric Evidence

Abstract: Analysis of the effects of public financing on private investment in R & D has been the object of numerous applied studies without it having been possible to arrive at a definite conclusion. In this paper the results of a meta-regression of econometric evidence on the relationship between public funding of R & D and private R & D expenditures is presented. After the creation of a data-base including all relevant studies and their results and characteristics, a meta-analysis was carried out to examine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(109 citation statements)
references
References 33 publications
2
96
0
3
Order By: Relevance
“…Among the many findings, some cases have showed complementarity and others substitution between public and private funds. An exhaustive review of the related literature can be found in David, Bronwyn and Toole (2000), García-Quevedo (2004) and Lööf and Hesmati (2005).…”
Section: Public Randd Funding and The Behaviour Perspective: A Review Omentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many findings, some cases have showed complementarity and others substitution between public and private funds. An exhaustive review of the related literature can be found in David, Bronwyn and Toole (2000), García-Quevedo (2004) and Lööf and Hesmati (2005).…”
Section: Public Randd Funding and The Behaviour Perspective: A Review Omentioning
confidence: 99%
“…Most of this work adopts one of three analytic approaches: the influence of policies on R&D input levels (Branstetter and Sakakibara 1998;Almus and Czarnitzki 2003;García-Quevedo 2004), the influence on innovation behaviour (Huggins 2001;Polt and Streicher 2005;OECD 2006) and the influence on the outcome of the innovation process (Branstetter and Sakkibara 1998;Klette and Moen 1999;Huggins 2001;Benfratello and Sembenelli 2002;Bayona-Sáez and García-Marco 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This literature analyses the impact of policy tools on firms' innovative performance indicators. The empirical evidence (David et al, 2000;García-Quevedo, 2004;Cerulli, 2010;Zúñiga-Vicente et al, 2014) has focused primarily on evaluating the impact of public funding on R&D inputs measured through R&D spending and R&D effort, and on R&D outputs such as patents, sales of new products or the number of new products and processes.…”
Section: Public Subsidies and Randd Employmentmentioning
confidence: 99%
“…David, Hall and Toole (2000) survey 32 studies and conclude that "the findings overall are ambivalent". Garcia-Quevedo (2004) conducts a meta-analysis of 74 results from 39 studies, and concludes similarly that "the econometric evidence … is ambiguous". Finally, Bronzini and Iachini (2011) list eleven papers published during the last decade and find that only half of them confirm a positive role for public R&D incentives.…”
Section: Introductionmentioning
confidence: 99%